The Application of Mobile GPS Probe Data on Detection of Real-Time Traffic Congestion Length: The Case Study of the Project for Improving Traffic Congestions in Bangkok through the Establishment of ATC System - TANSAWAT, Tithiwach; NISHINO, Ken; MATSUOKA, Seiya; BROUWER, Joroen; JANSUWAN, Sarawut; MASUJIMA, Tetsuji (Journal of the Eastern Asia Society for Transportation Studies, 2024)
This study focuses on enhancing the Area Traffic Control (ATC) system in Bangkok area by leveraging Floating Car Data (FCD) obtained from mobile GPS probe data. The aim is to supplement the existing stationary roadside detectors used to detect real-time traffic congestion and optimize traffic signal timings. By comparing the congestion lengths derived from processed FCD with those obtained through field surveys, the study demonstrates a high level of accuracy, with an RMSE of 99.3, surpassing the accuracy of the stationary detectors installed at approximately 200-meter intervals. Furthermore, by incorporating geometric conditions such as number of traffic lanes and intersection types into the regression model, the study proposes a slight adjustment to the estimated queue lengths, bringing them closer to the actual values. This approach overcomes the cost limitations of installing and maintaining additional detectors, thereby improving efficiency and effectiveness of the ATC system in managing traffic congestion in Bangkok.